2012
DOI: 10.7314/apjcp.2012.13.1.387
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Gestational Trophoblastic Neoplasia Patients Treated with 5-Fluouracil plus Actinomycin D

Abstract: The median number of cycles for each patient was two and only one case achieved remission while four of the cases were unresponsive. The toxicity was evaluated in 12 cycles. Common complications were uncomplicated myelosuppression and mucositis. In conclusion, this regimen revealed modest efficacy in a salvage setting with manageable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The treatment modalities include suction dilation and curettage and combination chemotherapy in case of malignancy (Manopunya et al, 2012;Oranratanaphan et al,2014). Invasive mole that follows complete and partial hydatiform mole is characterized with invasion of the molar villi to the myometrium.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment modalities include suction dilation and curettage and combination chemotherapy in case of malignancy (Manopunya et al, 2012;Oranratanaphan et al,2014). Invasive mole that follows complete and partial hydatiform mole is characterized with invasion of the molar villi to the myometrium.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be explained by the modality of treatment in GTN. Although hysterectomy were necessary in some cases, the majority of GTN patients could be cured by chemotherapy alone which can preserve uterus and ovaries (Pongsaranantakul and Kietpeerakool, 2009;Seckl et al, 2010;Manopunya and Suprasert, 2012;Ozalp et al, 2014). Previous study (Pinar et al, 2012)showed that hysterectomy had negative effects on body image and self-esteem in women affected by gynecologic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The FA regimen is effective in low-and high-risk GTN patients, but not in PSTT patients. Additionally, it may be administered as a primary chemotherapy regimen for the treatment of high-risk GTN patients (13,14). It is reported that the EMA/CO regimen is considered to be highly effective for the treatment of high-risk GTN, as it exhibits good efficacy and is well-tolerated by patients.…”
Section: Discussionmentioning
confidence: 99%